Performance and Operational Characteristics of Modified Anaerobic Hybrid Baffled (MAHB) Reactor Treating Low Strength Recycled Paper Mill Effluent (RPME) wastewater / Siti Roshayu Hassan, Nastaein Qamaruz Zaman and Irvan Dahlan - Hassan, Siti Roshayu; Qamaruz Zaman, Nastaein; Dahlan, Irvan (Research Management Institute (RMI), 2014)
The performance and operational characteristics of a laboratory scale modified anaerobic hybrid baffled (MAHB) reactor were studied using recycled paper mill effluent (RPME) wastewater. MAHB reactor was continuously operated at 35°C for 90 days with organic loading rate (OLR) increased from 0.14 to 0.57 g/L/dy. This present study demonstrated that the system was proficient in treating low strength RPME wastewater. Highest carbon oxygen demand (COD) removal were recorded up to 97% for an organic loading of 0.57 g /L/dy while effluent alkalinity assured that the system pH in the MAHB compartments were of great advantages to acidogens and methanogens respectively. Methane and biogas production rate shows increment as the load increases, which evidently indicated that the most significant approach to enhance gas production rates involves the increment of incoming substrate moderately. Variations of biogas and volatile fatty acid (VFA) in different compartments of MAHB reactor indicated the chronological degradation of substrate. The compartmental structure of MAHB reactor provided its strong ability to resist shock loads. From this present study, it shows the potential usage of MAHB reactor broadens the usage of multi-phase anaerobic technology for industrial wastewater treatment.